Here's the question you clicked on:
BrennaM
Quadratic Expressions
Your equation is:\[-\frac{1 }{ 2 }x^2- 2x-6\]Use the Quadratic formula:\[x = -b \pm \frac{ \sqrt{b^2 - 4ac} }{ 2a }\] Fill in the values: \[-(-2) \pm \frac{ \sqrt{-2^2 - 4(-\frac{ 1 }{ 2 })(-6)} }{ 2(-\frac{ 1 }{ 2 })}\] \[2 \pm \frac{ \sqrt{-2^2 - 4(-\frac{ 1 }{ 2 })(-6)} }{ 2(-\frac{ 1 }{ 2 })}\] -2^2 = 4 4(-1/2)(-6) = 12 1 * -1/2\[2\pm \frac{\sqrt{4 - 12} }{ -1 }\]\[2 \pm \frac{ \sqrt{-8} }{ -1 }\]\[2\pm \frac{ 2.83 }{ -1 }\]\[2\pm -2.38\] 2 + (-2.38) = -0.37 2 - (-2.38) = 2 + 2.38 = 4.38 So the two solutions for x are: x = -0.37 and x = 4.38
@BrennaM I hope this helps! (: